1995
DOI: 10.1016/s1078-5884(05)80057-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intermittent claudication: The impact on quality of life

Abstract: Unsupervised exercise programs are unlikely to significantly improve patient's quality of life. The benefits of surgery and angioplasty support a relaxation in the indications for investigation and treatment of claudicants. Patients with impaired perceived health should not be denied treatment on the basis of preintervention ankle pressure or walking distance alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
2
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 14 publications
3
90
2
2
Order By: Relevance
“…9,14,26 Similarly, PTA has been previously studied and shown to be beneficial to QoL. [18][19][20]27 However, ours is the first study to directly compare QoL following PTA and SEP in the treatment of IC. Ours is also the first study to directly compare these two treatments against combined therapy (PTA + SEP).…”
Section: Prwdmentioning
confidence: 84%
See 1 more Smart Citation
“…9,14,26 Similarly, PTA has been previously studied and shown to be beneficial to QoL. [18][19][20]27 However, ours is the first study to directly compare QoL following PTA and SEP in the treatment of IC. Ours is also the first study to directly compare these two treatments against combined therapy (PTA + SEP).…”
Section: Prwdmentioning
confidence: 84%
“…However, none of the included studies directly compared SEP and PTA. [17][18][19][20][21][22][23][24] There is no published literature of a three-way comparison between SEP, PTA, and SEP + PTA; thus, this study is the first of its kind.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of the quality of life of patients with intermittent claudication employed various general questionnaires, i.e. Short Form-36 [19,20], Nottingham Health Profile [21] or EuroQol [22]. As rightly pointed out by Chong et al [9], the non-specific character of these tools can skip certain aspects of the quality of life closely related to intermittent claudication, leading, in her opinion, to missing significant changes.…”
Section: Discussionmentioning
confidence: 99%
“…32 Numerous studies have shown that successful revascularization can improve the patient's QOL and may reduce cardiovascular events because the patient remains mobile. 33, 34 In spite of the increasing life expectancy, QOL has become one of the main concerns in daily practice for these disabled patients. Maintenance of good QOL and reduction of symptomatic clinical events are important goals both for patients with CLI and clinicians.…”
Section: Discussionmentioning
confidence: 99%